Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/978-3-319-49169-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Entrainment in Dialogues

Abstract: Abstract. This paper performs a global analysis of entrainment between dyads in map-task dialogues in European Portuguese (EP), including 48 dialogues, between 24 speakers. Our main goals focus on the acoustic-prosodic similarities between speakers, namely if there are global entrainment cues displayed in the dialogues, if there are degrees of entrainment manifested in distinct sets of features shared amongst the speakers, if entrainment depends on the role of the speaker as either giver or follower, and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
3
0
7
Order By: Relevance
“…Evidences of acoustic-prosodic entrainment between speakers per dialogue (globally) were presented by [19], in the same map-task corpus. Now, we aim at verifying if the same speakers also show similarities to each other but at turn exchanges (locally).…”
Section: Local Entrainment Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences of acoustic-prosodic entrainment between speakers per dialogue (globally) were presented by [19], in the same map-task corpus. Now, we aim at verifying if the same speakers also show similarities to each other but at turn exchanges (locally).…”
Section: Local Entrainment Resultsmentioning
confidence: 99%
“…In EP, only two studies have addressed adaptation between speakers, [18], and [19], both using a subset of the same maptask corpus used in this study. [18] found evidences of prosodic correlations (pitch concord effects) between Yes/No-questions and affirmative answers; and [19] found global entrainment expressed in different degrees, since speakers did not entrained with the same partners and in the same features. Results showed that, despite the role speakers were playing (giver or follower), they tended to display more sensitivity to some partners, which may reveal a stronger partner effect than a role effect.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Em PE, apenas três estudos analisaram adaptação acústico-prosódica entre falantes (Cabarrão et al, 2013(Cabarrão et al, 2016a(Cabarrão et al, , 2016b, sendo que todos utilizaram o mesmo corpus aplicado no presente trabalho. Cabarrão et al (2013;2016a) mostraram evidências de correlações prosódicas (efeitos de concordância de níveis de frequência fundamental -f0) entre perguntas sim/não e respetivas respostas afirmativas.…”
Section: Enquadramento Teóricounclassified
“…Estudos prévios sobre fala espontânea em Português Europeu (PE) mostraram que existe adaptação acústico-prosódica entre falantes a nível do diálogo (adaptação global), embora em diferentes graus: os falantes não se adaptam sempre aos mesmos interlocutores e seguindo as mesmas estratégias acústicoprosódicas (Cabarrão et al, 2016). O presente trabalho visa adicionar mais um nível à análise da adaptação acústico-prosódica em PE, especificamente observar como os falantes se adaptam a nível local, ou seja, enunciado a enunciado.…”
Section: Introductionunclassified
See 1 more Smart Citation